Perbandingan Pengaturan Label Produk Kosmetik Antara BPOM Indonesia dan FDA Amerika Serikat - Muryati, Afri; Cholil, Mochamad (Jurnal Hukum Ekualitas, 2026)
The rapid growth of the cosmetics industry demands effective product labeling regulations to protect consumers and ensure information transparency. Labels serve to convey essential details such as ingredients, benefits, usage instructions, and warnings. This study analyzes and compares the cosmetic labeling regulations of Indonesia’s BPOM and the United States FDA using a normative juridical method and a comparative approach. BPOM regulates labeling in detail through BPOM Regulation No. 18 of 2024, while the FDA refers to the Federal Food, Drug, and Cosmetic Act (1938) and the Fair Packaging and Labeling Act (1967). The differences lie in the substance of regulations, institutional structure, and notification systems, although both aim to provide accurate and non-misleading information to consumers. In conclusion, the labeling systems of both countries are complementary, and FDA practices may serve as a reference for Indonesia in enhancing digitalization and transparency in cosmetic labeling oversight.